A diagnostic approach that may help to discriminate inherited thrombocytopenia from chronic immune thrombocytopenia in adult patients. (17th August 2016) - Fiore, Mathieu; Pillois, Xavier; Lorrain, Simon; Bernard, Marie-Agnès; Moore, Nicholas; Sié, Pierre; Viallard, Jean-François; Nurden, Paquita
Abstract: Inherited thrombocytopenia (IT) is a heterogeneous group of rare diseases that are often confused with immune thrombocytopenia (ITP). The objective of this study was to supply clinicobiological elements that allow a distinction to be drawn between IT and chronic ITP. We then compared 23 adult patients with IT and 9 patients with chronic ITP. Our study revealed six discriminating criteria: (i) an age of discovery <34 years: positive predictive value (PPV) = 88.2% [63.6; 98.5], (ii) a family history of thrombocytopenia: PPV = 100.0% [82.4; 100.0], (iii) a personal history of bleeding: PPV = 100% [76.8; 100.0], (iv) a mean platelet volume >11 fL: PPV = 93.3% [68.1; 99.8], (v) an excess of giant platelets on blood smear: 100.0% [76.8; 100.0], and (vi) a percentage >44% of platelets with a surface area >4 µm 2 in electron microscopy: PPV = 83.3% [58.6; 96.4]. If at least three of these criteria were combined, it was possible to distinguish IT from chronic ITP with 91.3% [72.0; 98.9] sensitivity and PPV = 100.0% [66.4; 100.0] specificity. The secondary objective of this study was to assess the prevalence of potential IT diagnosis in patients with chronic thrombocytopenia of uncertain origin. Applying our diagnostic approach to a series of 20 cases allowed us to estimate that 40% of them could be suffering from IT. Finally, our diagnostic approach may help to correctly distinguish IT from chronic ITP, particularly in the context of macrothrombocytopenia.